Konjac glucomannan/cellulose nanofibers composite aerogel supported HKUST-1 for CO2 adsorption. (1st October 2022) - Sun, Jinqiang; Shang, Mengge; Zhang, Minna; Yu, Shimo; Yuan, Zhipeng; Yi, Xibin; Filatov, Serguei; Zhang, Jing
Abstract: Biomass aerogels are attractive in various applications owing to their inherent advantages of renewability, biodegradability and eco-friendly. Herein, a novel composite aerogel of konjac glucomannan (KGM)/TEMPO-oxidized cellulose nanofibers (TOCNF)@HKUST-1 (KTA@HKUST-1) is prepared through a facile vacuum impregnation method combined with the directional freeze-drying process, which using KGM and TOCNF as raw materials. The structural analyses disclose that the KTA@HKUST-1 has a hierarchical porosity, in which HKUST-1 can provide micropores for adsorption, while the meso -/macropores from KTA act as high-speed channels to improve diffusion and mass transfer rate to transport CO2 components into the micropores of HKUST-1. The experiment results of KTA@HKUST-1-10 (KTA@H10) show that the CO2 adsorption capacity can reach 3.50 mmol·g −1 at 1 bar and 298 K, and the adsorption capacity retention rate as high as 91.43% after 7 cycles. In addition, the CO2 /N2 adsorption selectivity of KTA@H10 can reach 18.42, which has an excellent potential for selective CO2 adsorption. Graphical abstract: Unlabelled Image